THE INFLENCES OF INFLUENCERS ON YOUTUBE AND INFLENCER-BRAND FIT AFFECTING CUSTOMER’ S THE DECISION TO PURCHASE PRODUCTS - Phatthana, Wanlapa; Prasomphong, Jirayus (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2026)
This article aimed to study 1) the levels of purchase decision importance, 2) the influence of social media influencers on product purchasing decisions, particularly through the influence of YouTuber advertisements, and 3) the factors of brand–influencer compatibility that affect consumers’ purchase decisions influenced by YouTubers’ advertising. This study employed quantitative research, grounded in theoretical concepts of influencer–brand congruence and consumer purchase decision-making. The data were collected from 385 people who had experience in watching video clips on the YouTube website. The instrument for collecting data was questionnaires. The questionnaires were dispensed online to 385 YouTube users; multiple regression showed that credibility (β=0.279), expertise (β=0.525), and influencer–brand fit (R²=0.647) significantly predicted purchase decisions. The research results were found as follows: 1) The level of importance in purchasing decisions is high, particularly regarding online advertising and satisfaction; 2) Influencer-related factors, such as credibility and expertise, were positively correlated with purchase decisions, and the coefficient of determination explained 63.9% of the variance; and 3) The compatibility between the influencer and the influencer–brand fit, with the coefficient of determination explained 64.7%, in terms of content consistency, personality, lifestyle, and product knowledge, was found to significantly influence consumer behavior and explain a substantial portion of the variance in purchasing decisions. These results highlight the crucial role of social media influencers as modern marketing communication agents capable of building trust, enhancing credibility, and effectively stimulating purchase decisions. The study provides valuable insights for brands in shaping targeted digital marketing strategies through appropriate influencer selection.